2004
DOI: 10.1016/j.jacc.2003.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of paravalvular regurgitation in the Artificial Valve Endocarditis Reduction Trial (AVERT) echocardiography study

Abstract: Excluding those patients who had initial prosthetic valve explant, the two-year echocardiographic follow-up of the AVERT cohort shows no statistically significant differences in the prevalence or severity of PVR in the Silzone-coated prosthetic valve compared with the conventional prosthetic valve. Further monitoring is warranted to determine whether these clinical outcomes remain similar on long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 18 publications
2
52
0
4
Order By: Relevance
“…Small paravalvular regurgitant jets are frequently (10% to 25% of cases) seen on intraoperative TEE before cardiopulmonary bypass weaning 78,79 and may significantly decrease or resolve after the injection of protamine or in the days, weeks, or months after operation as the healing process evolves. Moderate or severe paravalvular regurgitation is rare (1% to 2%) and requires returning to cardiopulmonary bypass for immediate correction.…”
Section: Paravalvular Regurgitationmentioning
confidence: 99%
“…Small paravalvular regurgitant jets are frequently (10% to 25% of cases) seen on intraoperative TEE before cardiopulmonary bypass weaning 78,79 and may significantly decrease or resolve after the injection of protamine or in the days, weeks, or months after operation as the healing process evolves. Moderate or severe paravalvular regurgitation is rare (1% to 2%) and requires returning to cardiopulmonary bypass for immediate correction.…”
Section: Paravalvular Regurgitationmentioning
confidence: 99%
“…Ten years after heart valve replacement, up to 50% of the patients require reoperation or die of complications related to the prosthetic heart valves. There is usually no difference between mechanical and biological prostheses, but the frequency and nature of the complications related to the prostheses vary according to type, model, and valve position, as well as to each patient's characteristics 4,[11][12][13][14][15] . By quantifying the comparative odds ratios between patients who presented varying degrees of prosthetic valve leak, the present study contributes to a better knowledge of its clinical outcome and provides information to guide therapies and establish prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…One case report documented recurrent endocarditis in a patient with a Silzone valve that required two subsequent replacements [161]. Follow-up studies found a higher rate of embolism in the early post-operative period after mitral valve replacement [162] and a non-significant increase in paravalvular leak diagnosed by echocardiogram at a mean of more than a year from valve replacement [163] with the Silzone valves. Other studies documented a significant increase in the need for reoperation secondary to paravalvular leaks, especially in the first two years after initial surgery [164][165][166].…”
Section: Heart Valvesmentioning
confidence: 99%